Markova O. Internal Structuringh of the Concept Patriotism: Metaphorical Models - Markova O. I. (Philological Treatises, 2020)
The theoretical and methodological concept of the thesis is based on the anthropocentric approach to the description of the linguistic phenomena that is fundamental in modern linguistics, which involves focusing the researcher’s attention on the analysis of the content of the lexical units through the prism of knowledge presented in the meanings of these units. Study of the explication of the concept of PATRIOTISM in the language of print media of Ukraine is caused by the urgent need for such an analysis. An important stage in terms of the cognitive approach was the process of creating metaphorical models, which is the presence of vocabulary that verbalizes the cognitive and analogous operations transposed from the conceptual scope of other concepts. Metaphorical models form an image - a mental unit, structured with a number of conceptual metaphors, which form a set of culturally predetermined relationships in the minds of the recipient. Creating an image and appealing to the imagination, the metaphor generates awareness, which generates the comprehension that the mind perceives, forming judgments about the concept of PATRIOTISM. Analyzing these models using frame-slot operations and activating the frame (the first level of the concept) through the mental data of the second level (slots), you can recreate the structure of those models that form the concept. Internal structuring of the concept of PATRIOTISM is carried out according to the scheme, which consists of the basic frames, forming a conceptual network of the information system. The structure of the model «PATRIOTISM – GAME» forms the frames «patriotism - a demonstrative toy» and «patriotism – absurd». The structure of the model «PATRIOTISM – LOVE» forms the frames «patriotism – love for the country» and «patriotism – the highest virtue». Using a metaphorical model instead of a direct nomination in a discourse, the author guides the recipient’s opinion in a given direction, attempts to impose his system of assessments and views.